ANOTACIONES SOBRE LOS ARTIODACTYLA, CARNIVORA, Y PERISSODACTYLA DEL PARQUE NACIONAL NATURAL CHINGAZA (1) (2013)
W e present the information taken from field and laboratory work, bibliography research and personal comunication oftheArtiodactyla, Carnívora and Perissodactylaspecies from Chingaza Natural National Park. We in elude information to each specie and its presents the comun noun, taxonomic description, its biology, ecology and ethology compendry, and your geographic distribution.lt' s important empahsize that eigtheen species reported in the park of this orders, the 85 percentits presentin extinction danger, higthlighting the necessity ofrealize management and gestion planes to find the recover and usefull reasonable of sorne thi·s species